Snow algae communities in Antarctica: metabolic and taxonomic composition. Issue 3 (27th February 2019) - Davey, Matthew P.; Norman, Louisa; Sterk, Peter; Huete‐Ortega, Maria; Bunbury, Freddy; Loh, Bradford Kin Wai; Stockton, Sian; Peck, Lloyd S.; Convey, Peter; Newsham, Kevin K.; Smith, Alison G.
Summary: Snow algae are found in snowfields across cold regions of the planet, forming highly visible red and green patches below and on the snow surface. In Antarctica, they contribute significantly to terrestrial net primary productivity due to the paucity of land plants, but our knowledge of these communities is limited. Here we provide the first description of the metabolic and species diversity of green and red snow algae communities from four locations in Ryder Bay (Adelaide Island, 68°S), Antarctic Peninsula. During the 2015 austral summer season, we collected samples to measure the metabolic composition of snow algae communities and determined the species composition of these communities using metabarcoding. Green communities were protein‐rich, had a high chlorophyll content and contained many metabolites associated with nitrogen and amino acid metabolism. Red communities had a higher carotenoid content and contained more metabolites associated with carbohydrate and fatty acid metabolism. Chloromonas, Chlamydomonas and Chlorella were found in green blooms but only Chloromonas was detected in red blooms. Both communities also contained bacteria, protists and fungi. These data show the complexity and variation within snow algae communities in Antarctica and provide initial insights into the contribution they make to ecosystem functioning.